2014
DOI: 10.11648/j.aff.20140305.14
|View full text |Cite
|
Sign up to set email alerts
|

Human-Wildlife Conflicts: Case Study in Wondo Genet District, Southern Ethiopia

Abstract: Abstract:The purpose of this research was to identify the type of human-wildlife conflicts and wild mammals that cause the conflict, determine the extent of damage and to provide a better understanding of the causes of human-wildlife conflict in Wondo Genet district. The study was carried out from December 2013 to June 2013. Four sample areas were selected to collect data on human-wildlife conflict; Gotu, Wosha Soyoma and Wethera Kechema villages and Wondo Genet College of Forestry and Natural Resources. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 6 publications
1
16
0
Order By: Relevance
“…Rapid human population growth enhanced human encroachment on previously wild and uninhabited areas for agricultural and other economic activities particularly in African countries. Another study conducted by Fenta (2014) in southern Ethiopia on the sample size of 30 respondents, 63.3% claimed that they encountered with snatching of food items by Baboons and Monkeys and 20% of the respondents indicated that they experienced destruction of property, 10% encounter human disruption when they were sleeping and 10% of the Impacts of Human-Wildlife Conflict…..1235…”
Section: Human Wildlife Conflict Have Become More Frequent and Severementioning
confidence: 99%
See 1 more Smart Citation
“…Rapid human population growth enhanced human encroachment on previously wild and uninhabited areas for agricultural and other economic activities particularly in African countries. Another study conducted by Fenta (2014) in southern Ethiopia on the sample size of 30 respondents, 63.3% claimed that they encountered with snatching of food items by Baboons and Monkeys and 20% of the respondents indicated that they experienced destruction of property, 10% encounter human disruption when they were sleeping and 10% of the Impacts of Human-Wildlife Conflict…..1235…”
Section: Human Wildlife Conflict Have Become More Frequent and Severementioning
confidence: 99%
“…Sharing and completion for limited resources will leads to HWC. Crop-riding by wild animals is a common problem all over the world (Fenta, 2014;Gandiwa et al, 2013;Gandiwa et al, 2012;Kate, 2012;Gusset et al,(2009). This conflict is worsening in areas where humans and wild animal's requirements overlap (Gandiwa et al, 2012).…”
mentioning
confidence: 99%
“…Human–wildlife conflict (HWC), which occurs when humans and wildlife harm or are a threat to each other in the course of pursuing their needs or interests, represents the most pervasive and complex challenge currently being faced by conservationists and wildlife managers around the world (Fenta, 2014; World Park Congress, 2003). It is a growing problem which threatens lives, livelihoods and the survival of wildlife throughout the world (Granados & Weladji, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Wondo Genet natural forest area, where the study on soil fungal community in relation to fire conducted, covers about 797 ha of natural forests land Belaynesh, 2002;Fenta, 2014). The forest is characterized by remnant Dry Afromontane forest patches Belaynesh, 2002;Fenta, 2014) and harbours important fauna and flora (Belaynesh, 2002;Fenta, 2014).…”
Section: Figure5 Location Of the Study Sitesmentioning
confidence: 99%
“…Wondo Genet natural forest area, where the study on soil fungal community in relation to fire conducted, covers about 797 ha of natural forests land Belaynesh, 2002;Fenta, 2014). The forest is characterized by remnant Dry Afromontane forest patches Belaynesh, 2002;Fenta, 2014) and harbours important fauna and flora (Belaynesh, 2002;Fenta, 2014). The climate is characterized by the Weyna-Dega agro-climatic zone, with a bimodal rainfall pattern: the main rainy season is in the summer and a lesser rainy season is in spring (Belay, 2016;Fenta, 2014).…”
Section: Figure5 Location Of the Study Sitesmentioning
confidence: 99%